Innenhochdruck-Umformen verstärkter Blech-Rahmenstrukturen - Tolazzi, Massimo (Friedrich-Alexander-Universität Erlangen-Nürnberg, 2008)
Modern lightweight concepts are characterised by a specific application of tailored materials, new production technologies as well as complex components. This work, in which Tailor Welded Blanks should be formed into complex frame structures faces up one of the main topics of Lightweight. Aim of this work was on the one hand to extend the field of application of sheet hydroforming, by means of fundamental investigations, to complex frame structures and at the same time to define suitable process strategies and process limits with the support of analytic and numeric methods. On the other hand the application of sheet hydroforming as a forming technology for Tailor Welded Blanks should be investigated aiming at the definition of general process design strategies for the productio